Compositional mapping of bitumen using local electrostatic force interactions in atomic force microscopy. (26th September 2016) - MAGONOV, SERGEI; ALEXANDER, JOHN; SURTCHEV, MARKO; HUNG, ALBERT M.; FINI, ELHAM H.
Summary: In recent years, many researchers have investigated bitumen surface morphology, especially the so‐called bee‐like structures, in an attempt to relate the chemical composition and molecular conformation to bitumen micromechanics and ultimately performance properties. Even though recent studies related surface morphology and its evolution to stiffness and stress localization, the complex chemical nature of bitumen and its time‐ and temperature‐dependent properties still engender significant questions about the nature and origin of the observed morphological features and how they evolve due to exposure to various environmental and loading conditions. One such question is whether the observed surface features are formed from wax or from the coprecipitation of wax and asphaltene. Our prior work was mainly theoretical; it used density functional theory and showed that the coprecipitation theory may not stand, mainly because wax–asphaltene interactions are not thermodynamically favourable compared to wax–wax interactions. This paper presents a comprehensive approach based on experiments to study surface morphology of bitumen and conduct compositional mapping to shed light on the origin of the bee‐like surface morphological features. We used Atomic Force Microscopy (AFM), with the main focus being on single‐pass detection and mapping of local electric properties, as a novel approach to enhance existing compositional mapping techniques. This method was found to be highly effective in differentiating various domains with respect to their polarity. The results of our study favour the hypothesis that the bee‐like features are mainly composed of wax, including a variety of alkanes.